Panel stochastic frontier analysis of profitability and efficiency of Turkish banking sector in the post crisis era - Aysan, Ahmet Faruk; Karakaya, Mustafa Mete; Uyanik, Metin (Journal of Business Economics and Management, 2011)
This paper examines the efficiency and its relation to profitability in Turkish banking sector by employing Panel Stochastic Frontier Approach. In the post crises period, extensive structural changes have taken place and a great number of new developments have occurred, affecting the efficiency of banking sector. This is the first study that employs panel stochastic frontier approach for banking efficiency in Turkey. In this research, both cost and profit efficiency measures are estimated for the panel data consisting of 32 banks between 2002–2007. Results suggest that there is cost efficiency gain and convergence in the efficiency levels of banks. As another interesting result, foreign banks are less efficient and state banks are more efficient. This paper also analyzes the relation between efficiency and profitability and finds no robust relation between them. However, the bank size matters more for profitability. Article in English. Turkijos bankų sektoriaus veiklos pelningumo ir efektyvumo analizė pokriziniu laikotarpiu Santrauka. Autoriai nagrinėja Turkijos bankų veiklą, t. y. jų pelningumą bei efektyvumą pokriziniu laikotarpiu. Šis laikotarpis buvo pasirinktas todėl, kad atsirado daug įvairių struktūrinių pokyčių, kurie turėjo įtakos bankininkystės sektoriaus efektyvumui. Tyrimui buvo pasirinkti 32 Turkijoje veikiantys bankai (jų veiklos rodikliai prieš ekonominę krizę ir po jos). Rezultatai rodo, kad Turkijoje veikiančių užsienio komercinių bankų veikla yra mažiau efektyvesnė nei valstybinių. Taip pat autoriai analizuoja bankų veiklos efektyvumo ir pelningumo santykį, tačiau, kaip rodo gauti rezultatai, stipraus ryšio tarp jų nėra. Reikšminiai žodžiai: efektyvumas, pelningumas, komerciniai bankai, nacionaliniai bankai, Turkija